2018
DOI: 10.1016/j.dam.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow connectivity of Moore cages of girth 6

Abstract: Let G be an edge-colored graph. A path P of G is said to be rainbow if no two edges of P have the same color. An edge-coloring of G is a rainbow t-coloring if for any two distinct vertices u and v of G there are at least t internally vertex-disjoint rainbow (u, v)-paths. The rainbow t-connectivity rc t (G) of a graph G is the minimum integer j such that there exists a rainbow t-coloring using j colors. A (k; g)-cage is a k-regular graph of girth g and minimum number of vertices denoted n(k; g). In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chartrand et al [20] showed that the rainbow 3connectivity of the (3; 6)-cage (the Moore cage known as Heawood graph) is between 5 and 7 inclusive. Recently, Balbuena et al [21] proved that it is not 5, and they bounded the rainbow -connectivity of ( ; 6)-cages as follows: if is a Moore ( ; 6)-cage, then…”
Section: Introduction and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chartrand et al [20] showed that the rainbow 3connectivity of the (3; 6)-cage (the Moore cage known as Heawood graph) is between 5 and 7 inclusive. Recently, Balbuena et al [21] proved that it is not 5, and they bounded the rainbow -connectivity of ( ; 6)-cages as follows: if is a Moore ( ; 6)-cage, then…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…If is a ( , 6)-cage, then for = 3, = 4, and = 5, respectively, we have 3 ( ) ≤ 7, 4 ( ) ≤ 13, and 5 ( ) ≤ 21, respectively. In this paper we use a genetic algorithm to search for rainbow -colorings of ( ; 6)-cages with = 3 and = 4 [21] in order to see if the upper bound for ( ) can be improved.…”
Section: Introduction and Definitionsmentioning
confidence: 99%